2013
DOI: 10.1097/hjh.0b013e32835f955c
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone improves endothelial and cardiac autonomic function in non heart failure hemodialysis patients

Abstract: Low-dose spironolactone therapy in clinically stable non heart failure hemodialysis patients is associated with favorable effects on cardiovascular parameters known to adversely affect survival, such as endothelial dysfunction and heart rate variability. Spironolactone treatment might benefit long-term cardiovascular outcome of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 36 publications
2
34
1
2
Order By: Relevance
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full-text screening, one article was excluded as no data of serum potassium for the control group was provided. 21 Eleven studies were reported in this systematic review, among which five studies were RCTs [22][23][24][25][26] and six were non-randomized studies [27][28][29][30][31][32] ( Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…Matsumoto et al 32 reported that after administration of spironolactone at a dose of 25 mg daily for 6 months, there was a significant rise in serum potassium after spironolactone treatment (5.18 ± 0.72 vs. 4.96 ± 0.72 mmol/L, p50.05). Taheri et al, 23 Flevari et al 30 and Gross et al 22 reported a significant rise in the serum potassium level after administration of MRAs. These investigators administered MRAs at larger doses (no less than 50 mg thrice a week).…”
Section: Effect Of Mra On the Predialysis Potassium Levelmentioning
confidence: 99%
“…Thus, potassium secretion from the intestine is increased in patients with advanced CKD or on dialysis therapy [29,34,35], and mineralocorticoid receptor blockers are reported to suppress this mechanism [38]. Indeed, several studies have reported that the administration of spironolactone is associated with increased incidence of hyperkalemia in patients on maintenance hemodialysis therapy [63][64][65] although pronounced hyperkalemia (serum potassium ≥ 6 mEq/L) does not occur commonly [66]. Notably, there are also reported a substantial number of studies showing that spironolactone does not cause significantly higher levels of serum potassium in patients on hemodialysis [47][48][49] or peritoneal dialysis therapy [50,51,67,68], when compared with placebo (Table 1).…”
Section: Aldosterone Blockade In Ckdmentioning
confidence: 99%
“…Another research group reported a small-sized study with 14 HD patients without heart failure who received low-dose spironolactone at 25 mg × 3/week. After 4 months, blood pressure control, reactive hyperemia, and heart rate variability were significantly improved, while LV dimensions or mass were not improved [50]. Feniman-De-Stefano et al [51] conducted a small-sized randomized, double-blinded, placebo-controlled study in which 17 HD patients were divided into 2 groups.…”
Section: Effects On Cardiovascular Diseasementioning
confidence: 99%
“…Flevari et al [50] 14 HD patients Spironolactone 25 mg × 3/week 4 months Blood pressure controlled, the reactive hyperemia and heart rate variability improved. LV dimensions and mass were not improved.…”
Section: Risk Of Hyperkalemiamentioning
confidence: 99%